PATIENT PERCEPTION RELATED TO URODYNAMIC TESTING: A QUESTIONNAIRE BASED STUDY - Astram, Ari; Rahardjo, Harrina Erlianti (Indonesian Journal of Urology, 2018)
Objective: Urodynamic test is a series of test to evaluate the bladder function including voiding and storage physiology. Several previous studies have found that urodynamic testing had association with physical and emotional discomfort. The primary goal of this study was to determine the parameters of anxiety, pain, and shame related to urodynamic testing. Material & Method: From June 2014 to June 2015, a total of 57 consecutive patients who underwent urodynamic study were included in the present study, consisting of 20 men and 37 women. They have completed the questionnaire before and after urodynamic study. Patients were requested to answer four questions related to pain, embarrassment, anxiety, and knowledge related to urodynamic test. Results: Overall, most of the patients felt not at all and nearly not anxious before urodynamic study. Thirty percent of patient thought that there would be moderate pain when the urodynamic test is performed. Majority of patients (68% of patients) felt no embarrassment prior to the test. Overall, patients felt better after urodynamic study in terms of anxiety and pain. Parameter of embarrassment significantly increased after the test. Patient perception of anxiety and pain before urodynamic test are not significantly different with perception after urodynamic test. Conclusion: Urodynamic tests are very well tolerated by men and women. Majority of patients felt better after urodynamic test according to pain and anxiety score. No statistical difference in level of pain and anxiety between before and after the procedure, while parameter of embarrassment was significantly higher after the test was done.